Effectiveness of Affective-Reconstructive Couple Therapy on Marital Conventionalization and Global Distress - Danlian Namagardi, Harayer; Farzad , Vlialah; Nooranipoor , Rahmatollah (Shahroud Journal of Medical Sciences, 2021)
Background: This study aimed to investigate the effectiveness of couple therapy based on affective reconstruction, which is one of the special approaches in couple therapy, on marital conventionalization and global distress. Methods: The design of the present study was quasi-experimental and pre-test-post-test with a control group. The statistical population of the present study was all couples aged 25 to 45 years in district 3 of Tehran who had been referred to Siavoshan and Avaei Daroon counseling centers. 16 couples aged 25 to 45 years in two groups were selected by purposive sampling. All couples in the experimental (n=8) and control (n=8) groups completed the Snyder (1979) Married Satisfaction Questionnaire. The intervention was performed in the form of 15 sessions (1 hour per week) and then in the last post-test session of the subjects. After execution and data collection, data were analyzed by MANCOVA multivariate analysis of covariance using SPSSV19 software. Results: The results showed that couple therapy based on affective reconstructive approach had a significant effect on marital conventionalization and global distress (η=0.456, F=2.27 (27,2), Pvalue<0.001). Also, the results showed that couple therapy based on emotional reconstruction on marital conventionalization (η2 = 0.326, F=1.286 (28,1), Pvalue<0.001) and global distress had a significant effect (η2 = 0.268, F=10.267 (28,1), Pvalue<0.003). Conclusions: Therefore, educating psychotherapy programs based on affective reconstructive approach and such methods to psychologists, health professionals, couple therapists, and family counselors to improve marital conventionalization and global distress can be effective. Keywords: Couple therapy, Affective-reconstructive, Marital conventionalization, Global distress.